Fossil constraints on the origin and evolution of Platyhelminthes are surprisingly concordant with modern molecular phylogenies - Kenneth De Baets; Paula Dentzien-Dias; John Warren Huntley; Maarten P.M. Vanhove; Weronika Łaska; Aleksandra Skawina; Niels W.L. Van Steenkiste; Karina Vanadzina (Zoologia (Curitiba))
ABSTRACT Trace fossils preserved with fossil worm-shaped remains suggest the presence of free-living flatworms during the Ordovician at the latest and their occurrence in terrestrial environments during the Permian. The presence of hooks associated with acanthodian and placoderm fishes indicates the existence of parasitic monopisthocotyleans, with a simple life cycle, during the Devonian. The presence of eggs in shark coprolites suggests the occurrence of eucestode tapeworms, with complex life cycles, during the Permian, possibly even earlier in the Carboniferous. Fossil evidence for trematode flatworms, also with complex life cycles, is more recent, including diverse findings associated with bivalves, lizards, and coprolites of archosaurs in terrestrial environments between 126 and 76 Ma in the Cretaceous. Convincing evidence for gymnophallid trematodes in marine environments appears in the Eocene, with an earlier occurrence in Cretaceous freshwater environments. This chronological pattern of first appearance (Turbellarians > Monopisthocotylea > Cestoda > Trematoda) is surprisingly concordant with some recent molecular phylogenetic analyses. Further evidence to test these hypotheses could be obtained by conducting systematic screenings for resistant remains of platyhelminths such as hooks and eggs as well as characteristic traces such as trails or shell concretions preserved with their producers. Additional study and scrutiny are particularly needed for trace fossils attributed to free-living flatworms that are not associated with their producers. We make recommendations on how different constraints on flatworm evolution can be interpreted and used in future studies.